Peningkatan Kualitas Sumber Data Manusia dalam Manajemen Berbasis Sekolah: Jalan Menuju Pendidikan Berkualitas - Hanapiah, Frisian Nur; Amalia, Larissa Suci; Daud, Muhammad Rafi Bahirudin; Sabirah, Ruzaina; Ardiansyah, Saiful; Prihantini , Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Improving the quality of Human Resources (HR) through the implementation of School-Based Management (SBM) is a strategic step to realize quality education. MBS authorizes schools to manage resources openly and involve all relevant parties. This research aims to explore the future potential and long-term impact of the implementation of SBM and human resource development in improving the overall quality of education. The data in this study were collected through in-depth interviews, direct observation, and document analysis. Data analysis was carried out thematically with an interpretive approach. The results of the analysis show that the success of SBM is highly dependent on the quality of human resources, especially school principals, teachers, and education staff. Efforts to improve the quality of human resources are carried out through various strategies, such as training, certification, professionalism development, and collaboration with external parties. These programs are effective in strengthening teachers' ability to create learning environments that are innovative, supportive, and responsive to student needs. In addition, the provision of motivation, incentives, and support from various parties also plays a role in increasing the work spirit and dedication of educators